Manajemen Pembiayaan SMKN 1 Pangandaran dalam Meningkatan Kompetensi Wirausaha Siswa - Aini Ali Agustini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
SMKN 1 Pangandaran faces limited employment opportunities for graduates, leading to the creation of business units to boost students' entrepreneurial skills. These units serve both as business opportunities and practical learning platforms. This study aims to explore the financial management practices at SMKN 1 Pangandaran and assess how they contribute to developing students' entrepreneurial competencies. Utilizing a descriptive qualitative approach, the research involved observations, interviews, and documentation, grounded in financial management theories by Nanang Fattah and entrepreneurial indicators by Peter Drucker. The study finds that transparent and accountable financial management, supported by BOS Pusat, BOPD, and BLUD, positively impacts entrepreneurial education. Business units like Teaching Factory provide hands-on business experience, enhancing students' managerial and soft skills. The program fosters technical expertise, leadership, and problem-solving abilities, creating a conducive learning environment. SMKN 1 Pangandaran's approach can serve as a model for other institutions in advancing student entrepreneurship.